Molecular dynamics simulations of the interaction between OH radicals in plasma with poly-β-1-6-N-acetylglucosamine - YANG, Shuhui; ZHAO, Tong; CUI, Jingxian; HAN, Zhiyun; ZOU, Liang; WANG, Xiaolong; ZHANG, Yuantao (Plasma science & technology, 2020)
Cold atmospheric plasma shows a satisfactory ability to inactivate bacterial biofilms that are difficult to remove using conventional methods in some cases. However, the researches on the inactivation mechanism are not quite sufficient. Poly-β-1-6-N-acetylglucosamine (PNAG), which is one of the important components in some biofilms, was used as the research subject, and the related mechanism of action triggered by different concentrations of the OH in plasma was studied using reactive molecular dynamics simulations. The results showed that OH radicals could not only trigger the hydrogen abstraction reaction leading to cleavage of the PNAG molecular structure, but undergo an OH addition reaction with PNAG molecules. New reaction pathways appeared in the simulations as the OH concentration increased, but the reaction efficiency first increased and then decreased. The simulation study in this paper could, to some extent, help elucidate the microscopic mechanism of the interaction between OH radicals in plasma and bacterial biofilms at the atomic level.